Food Estate Policy in Overcaming Food Security in Indonesia in The Era of Covid 19 Maqashid Shariah Perspective - Ilham Putra Usmayani; Andi Bisyriani; Kurniati Yunus; Dian Resky Pangestu; Restu Fitria Ningsih (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The year 2020 marked a significant global impact due to the COVID-19 pandemic, affecting various sectors of life, including agriculture in Indonesia. This study aims to evaluate the implementation of the food estate program as a national food security strategy in Labuha Village, South Halmahera Regency, and its alignment with the maqasid sharia concept. Using a juridical-empirical approach, this research incorporates primary data from interviews with local residents and secondary data from relevant sources. The findings reveal that the food estate program, designed to address food crises during the pandemic, received a positive response from 75% of Labuha Village residents. The program supports various economic and social aspects, with 45% of the population engaged in farming utilizing vacant land for hydroponic cultivation, which also helps reduce the spread of COVID-19. From the perspective of maqasid sharia, 80% of government policies are in line with sharia principles, particularly in safeguarding life and providing halal food. This study underscores the importance of integrating food security policies with sharia values to achieve sustainable welfare amidst a crisis